2015
DOI: 10.1126/science.aaa6442
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of room-temperature ferroelectricity at reduced dimensions

Abstract: The enhancement of the functional properties of materials at reduced dimensions is crucial for continuous advancements in nanoelectronic applications. Here, we report that the scale reduction leads to the emergence of an important functional property, ferroelectricity, challenging the long-standing notion that ferroelectricity is inevitably suppressed at the scale of a few nanometers. A combination of theoretical calculations, electrical measurements, and structural analyses provides evidence of room-temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
212
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(225 citation statements)
references
References 52 publications
10
212
0
3
Order By: Relevance
“…Привнесенное механическими напряжениями искажение элементарных ячеек в прослойке титаната стронция, прилегающей к межфазной границе, обус-ловливает появление в ней спонтанной поляризации, вектор которой направлен перпендикулярно плоскости подложки. Особенности формирования сегнетоэлектри-ческой фазы в наноразмерных пленках STO активно обсуждаются в настоящее время в литературе [13,14]. При высокой концентрации вакансий кислорода в под-ложке и существенной концентрации атомов лантана в приграничном слое подложки одновременно с появле-нием спонтанной поляризации в прослойке подложки у межфазной границы возникает деполяризующее поле, Физика твердого тела, 2018, том 60, вып.…”
Section: экспериментunclassified
“…Привнесенное механическими напряжениями искажение элементарных ячеек в прослойке титаната стронция, прилегающей к межфазной границе, обус-ловливает появление в ней спонтанной поляризации, вектор которой направлен перпендикулярно плоскости подложки. Особенности формирования сегнетоэлектри-ческой фазы в наноразмерных пленках STO активно обсуждаются в настоящее время в литературе [13,14]. При высокой концентрации вакансий кислорода в под-ложке и существенной концентрации атомов лантана в приграничном слое подложки одновременно с появле-нием спонтанной поляризации в прослойке подложки у межфазной границы возникает деполяризующее поле, Физика твердого тела, 2018, том 60, вып.…”
Section: экспериментunclassified
“…But whether such a scenario should manifest itself in the switching mechanism which involves nucleation and growth of favorable domains or the coherent rotation of the polar domains remains unclear. On the other hand, a recent experiment by Lee et al 26 used naturally existing polar nanoregions formed due to local nanoscale inhomogeneities such as Sr vacancies to stabilize a net switchable polarization in nanometer thick epitaxial, strain free SrTiO 3 film. The EDS study carried out by us also reveals Sr deficiencies at nanoscale.…”
Section: Raman Spectroscopy Measurementsmentioning
confidence: 99%
“…Whether these nanoclusters can give rise to net macroscopic electric polarization is still an open question. Very recently, however, Lee et al have come out with evidence that alignment and stabilization of these polar nanoregions in ultra-thin SrT iO 3 film is indeed possible under electric field which can result in net ferroelectric polarization at room temperature 26 although the dynamics of the switching process is not elaborated. Interestingly, majority of the experiments on SrT iO 3 have been carried out without using any electrode material which does not help establish a holistic insight into the subject since the electrical boundary conditions at the interface influence the ferroelectric phase.…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications have reported important approaches of bulk and nanostructure ferroelectric materials at room temperature [1][2][3][4][5] Magnetoelectric multiferroic materials enable fast electrical writing and magnetic reading, and can thus be applied to non-volatile random access memory. However, fast electrical writing and magnetic reading exist more difficulties in single crystalline structure bulk materials because ferroelectricity need closed-shell d 0 or s 2 cation and ferromagnetic need open-shell d n with unpaired electron.…”
mentioning
confidence: 99%
“…By DFT calculations and experimental measurements, they found that the local structures conducting polar nanodomains at room-temperature are embedded in insulating domain boundaries, which can form "nanocapacitor" domains. The stable capacitance offers "nanobits," which have potential applications in high-density information storage at room temperature.Ferroelectric materials have important nanoelectronic applications at room temperature [3]. Many researchers have demonstrated that nanostructures will enhance the performance of nanodevices [2][3][4].…”
mentioning
confidence: 99%